IDENTIFICATION OF PUTATIVE HYBRIDS AND NATURAL LINEAGES IN GENUS POTAMOGETON REVEALED BY CHLOROPLAST AND NUCLEAR DNA MARKERS - Tao Zhang; Jianbo Wang (Pure and Applied Biology, 2012)
Phylogenetic relations of hybrids and non-hybrid species in the genus Potamogeton were reconstructed based on three spacers and one intron of chloroplast sequences and nuclear sequences of 5S-NTS. By comparing the phylogenetic relationships of subgenus Potamogeton with floral size, we propose that the split in the two main lineages reflects an early differentiation of flower size, perhaps due to the shift from out- to in-breeding; we also presume that more complex evolutionary processes exist in subgenus Potamogeton based on present study. As natural hybridization plays a fundamental role in the evolution of Potamogeton, frequently resulting in the formation of entirely new species, compelling evidence supports the hybrid origin of species: P. anguillanus, P. hubeiensis, P. kamogawaensis, and the triple hybrid-P. sp. hybrid. Incongruence between nuclear and plastid tree indicated that introgression might had occurred from subgenus Coleogeton to subgenus Potamogeton